2017
DOI: 10.1016/j.chemosphere.2016.12.097
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric assay to assess short-term effects of personal care products on the marine microalga Tetraselmis suecica

Abstract: Large quantities of personal care products (PCPs) are used daily and many of their chemical ingredients are subsequently released into marine environments. Cultures of the marine microalga Tetraselmis suecica were exposed for 24 h to three emerging compounds included in the main classes of PCPs: the UV filter benzophenone-3 (BP-3), the disinfectant triclosan (TCS) and the fragrance tonalide (AHTN). Concentrations tested, expressed as cellular quota (pg cell), ranged from 5 to 40 for BP-3, from 2 to 16 for TCS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…The effect of BP3, DHHB and OC was significant at 100 µg/L and above. A similar decreased esterase activity was reported for C. reinhardtii exposed to BP3, although at concentrations in the mg/L range [21,43]. For DHHB, the effect was only observed for the microalgae and for the esterase activity but not for other parameters.…”
Section: Impact On Cell Metabolic Activitysupporting
confidence: 80%
“…The effect of BP3, DHHB and OC was significant at 100 µg/L and above. A similar decreased esterase activity was reported for C. reinhardtii exposed to BP3, although at concentrations in the mg/L range [21,43]. For DHHB, the effect was only observed for the microalgae and for the esterase activity but not for other parameters.…”
Section: Impact On Cell Metabolic Activitysupporting
confidence: 80%
“…Esterases involved in the FDA assay turn over on a time frame of several hours (Jochem, 2000). Therefore, this technique seems appropriate to detect changes in metabolic activity on a day-to-day or even shorter basis, which makes it well suited to monitor short-term phytoplankton responses to environmental changes or to diverse pollutants (Esperanza et al, 2015;Franklin et al, 2001;Prado et al, 2009;Seoane et al, 2017a;Seoane et al, 2017b). Our results showed that, with more subtle measurements, we can detect the impact of MP.…”
Section: Decrease In Esterase Activity As An Early Response To Mp Expmentioning
confidence: 80%
“…Esterase activity in C. neogracile cells was studied using the fluorescein diacetate (FDA) cytometric assay previously described in Seoane et al (2017b). Cells were incubated with FDA at a final concentration of 6 μM for 10 min at room temperature in the dark.…”
Section: Esterase Activitymentioning
confidence: 99%
“…In addition to cell density measurements, flow cytometry can be used to analyse several morphological parameters, such as relative cell size and complexity and relative fluorescence, which is related to pigment content (Marie et al, 2005;Stachowski-Haberkorn et al, 2013;Mansano et al, 2017). Using fluorescent dyes specific to particular physiological functions, several studies have shown the usefulness of flow cytometry to indicate the toxicity of certain chemicals to microalgae (Prado et al, 2009(Prado et al, , 2012Rioboo et al, 2011;Stachowski-Haberkorn et al, 2013;Seoane et al, 2014Seoane et al, , 2017Esperanza et al, 2015;Dupraz et al, 2016;González-Pleiter et al, 2017). The most commonly investigated physiological functions in these studies are viability, general metabolic activity (often measured by non-specific esterase activity) and reactive oxygen species (ROS), whose accumulation following exposure to certain contaminants can cause oxidative stress and thus cell damage.…”
Section: A C C E P T E Dmentioning
confidence: 99%